Analisis Nilai Tambah dan Strategi Pengembangan Usaha pada Agroindustri Kukis Bawang â€œDiyanahâ€ di Kelurahan Jrebeng Kulon Kecamatan Kedupok Kota Probolinggo - Nisyak, Umi Khoirun; Supriono, Agus (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2024)
Probolinggo City have an agroindustry that produces onion cookies that agroindustry name is the â€œDiyanahâ€ business. This research aims to determine the added value and added value ratio of the processing of shallots into fried onions, fried onions into onion cookies and shallots into onion cookies, and business development strategy. The research method used is analytic and descriptive methods. In collecting the data used, namely using structured interview methods and documentation. The data analysis method is using the Hayami method and using the SWOT analysis method. Result from this research shows that in the processing of shallots into fried onions has an added value of IDR 1,085.53/kg with a ratio of 2.89%, added value in the process of processing fried onions into onion cookies amounted to IDR 231,337.62 / kg with a ratio of 53.33%, The added value in the process of processing shallots into onion cookies is IDR 36,241.31 / kg with a ratio of 36.24%. The alternative strategy that can be considered appropriate for the development of the onion cookie agro-industry business in Jrebeng Kulon Village, Kedopok District, Probolinggo City is SO, by utilizing the power to gain opportunities